Types of goals scored over the course of a match: An analysis of the Australian national soccer league - Abt, G. A.; Dickson, G.; Mummery, W. K.; Rowsell, G. (1999)
We have previously reported that goal scoring in soccer is time dependent (Abt et al., 1999). The mechanisms involved in this phenomenon are most probably multifactorial, although physical and mental fatigue appear to contribute to the process. Given this link, it is tempting to suggest that as a match progresses, an increase in the frequency of penalties and own goals would be observed, due to an increase in the number of mistakes made. Additionally, previous research has identified that 77% of the goals scored in the final 15-minute period either give or confirm a win. To address these issues in an Australian context, five seasons of the Australian national soccer league (1994/95 - 1998/99) were analysed. The analysis was conducted in two parts: (a) all goals scored across the five seasons (n = 2670) were analysed to determine the frequency of penalty and own goals scored per 15-minute period and (b) the last goal scored in the final 15-minute period of each match (n = 422) was identified to determine the effect of that goal on the outcome of the match. A normal goal was defined as one being scored from general play; a confirmatory goal was defined as being one which increased a teams lead and a consolation goal was defined as being one which decreased the difference between the two teams. Results revealed an increase in the frequency of penalty goals scored in the second half (n = 101) compared to the first half (n = 55). There was little difference in the frequency of own goals scored across time periods. The second analysis revealed that during the final 15-minute period, the frequency of winning, drawing, confirmatory and consolation goals were 112, 68, 174 and 68 goals, respectively. An increase in the frequency of penalty goals scored in the second half suggests that players are either taking more risks in defence during this period, or that there is an increase in the number of technical errors leading to fouls being committed in the penalty area. The results of the second analysis confirm those of previous research, with 68% of those goals identified from the final 15-minute period of the match either giving or confirming a win. Alternatively, 57% of those goals identified from the final 15-minute period had no effect on the outcome of the match. The frequency of confirmatory and drawing goals identified during the final 15-minute period may help to explain the suggestion that a losing team engages in riskier play toward the end of a match in order to score. However, the results of the present study show that more confirmatory goals are scored than drawing goals during the final 15-minute period, creating doubt as to the efficacy of such a strategy.